Real-world assessment of quality-of-life in patients with breast cancer treated with adjuvant endocrine therapy - ARIKAN, RUKİYE; BAŞOĞLU TÜYLÜ, TUĞBA; DANE, FAYSAL; YUMUK, PERRAN FULDEN; KÖSTEK, OSMAN (My University, 2022)
Objective: The aim of this study was to investigate quality-of-life (QoL) in breast cancer (BC) patients treated with adjuvant endocrine therapy (AET). Methods: We designed a cross-sectional study of 233 BC patients treated with AET and used the Functional Assessment of Cancer Therapy - Breast questionnaire. Results: No significant difference was observed between endocrine agents. Duration of AET did not affect QoL. In the entire cohort, multivariate analysis determined age (p = 0.034) and switching treatment from tamoxifen to aromatase inhibitors (p = 0.049) as significant positive coefficients of QoL, while comorbidity (p = 0.072) tended to be associated with lower scores. Education level (p = 0.001) and chemotherapy (p = 0.04) were significant predictors of QoL in the tamoxifen group, while comorbidity (p = 0.04), surgery type (p = 0.02), radiotherapy (p = 0.006) and stage (p = 0.009) had a significant impact on QoL in aromatase inhibitors group. Conclusion: Evaluating the well-being of BC patients by QoL questionnaires is of great importance to identify particular subgroups that may require supportive care.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Oncology; ONKOLOJİ; Klinik Tıp; Klinik Tıp (MED); ONCOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); adjuvant endocrine therapy; breast cancer; FACT-B; FACT-G; quality-of-life; FUNCTIONAL ASSESSMENT; POSTMENOPAUSAL WOMEN; SYMPTOM BURDEN; TAMOXIFEN; SURVIVORS; EXEMESTANE; OUTCOMES; IMPACT; TRIAL